Gender-Based Violence in Egypt: Analyzing Impacts of Political Reforms, Social, and Demographic Change. (March 2013) - Ambrosetti, Elena; Abu Amara, Nisrin; Condon, Stéphanie
Over recent decades, Egypt has witnessed developments in gender equality. This article discusses recent changes relating to violence against women within this context. Statistical data from the Egyptian DHS surveys is used to describe trends in reported violence and in attitudes toward marital abuse, as well as to examine the survey tools used to measure violence. While findings reflect a growing awareness regarding the issue, the number of women reporting spousal violence remained stable during the study period. The results are contextualized within the political and social debate in which NGO's and women's rights activists play a central role.